2011
DOI: 10.1371/journal.ppat.1002267
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Viral By-Product dsRNA or Coxsackievirus B5 Triggers Pancreatic Beta Cell Apoptosis via a Bim / Mcl-1 Imbalance

Abstract: The rise in type 1 diabetes (T1D) incidence in recent decades is probably related to modifications in environmental factors. Viruses are among the putative environmental triggers of T1D. The mechanisms regulating beta cell responses to viruses, however, remain to be defined. We have presently clarified the signaling pathways leading to beta cell apoptosis following exposure to the viral mimetic double-stranded RNA (dsRNA) and a diabetogenic enterovirus (Coxsackievirus B5). Internal dsRNA induces cell death via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 62 publications
1
55
0
Order By: Relevance
“…As a result, Mcl-1 levels are expected to decline. This scenario has been confirmed recently in invitro studies where it was shown directly that treatment of cultured beta cells with the viral double stranded RNA (dsRNA) mimetic, polyinosinic:polycytidylic acid (poly-I:C; which will activate PKR) led to rapid loss of Mcl-1 from the cells [14].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As a result, Mcl-1 levels are expected to decline. This scenario has been confirmed recently in invitro studies where it was shown directly that treatment of cultured beta cells with the viral double stranded RNA (dsRNA) mimetic, polyinosinic:polycytidylic acid (poly-I:C; which will activate PKR) led to rapid loss of Mcl-1 from the cells [14].…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, to maintain adequate levels of Mcl-1 within the cell, the protein must be synthesised and replenished at a rate that is at least equal to its rate of degradation. Under conditions in which PKR is activated, the translation initiation factor eIF2α becomes phosphorylated, leading to translational arrest and thereby to a reduction in the rate of Mcl-1 synthesis [14,28]. As a result, Mcl-1 levels are expected to decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we took advantage of this situation to study the expression of a labile, anti-apoptotic protein, Mcl-1, in VP1+ (PKR+) islet cells. Mcl-1 is constitutively expressed at high levels in most beta cells [60] and from in vitro studies, the protein is understood to be a critical determinant of beta cell fate in response to stressors (such as proinflammatory cytokines and viral infection) [65]. Importantly, we observed that Mcl-1 was selectively depleted from beta-cells expressing VP1 and PKR suggesting that these individual cells might then be rendered more sensitive to the detrimental effects of the pro-inflammatory mileu existing within inflamed islets [60].…”
Section: (And Unpublished Results Richardson Et Al)mentioning
confidence: 99%
“…Although common agents of acute infections, enteroviruses, and particularly coxsackievirus B types, may also be involved in the pathogenesis of type 1 diabetes (Craig et al, 2013). It has been suggested that enteroviruses either directly infect pancreatic islet b-cells leading to cell destruction (Colli et al, 2011;Ylipaasto et al, 2004) or trigger a T-cell immune response, which evokes proinflammatory mediators and the activation of the immune cells, which attack and destroy b-cells in pancreatic islets (Eizirik et al, 2009;Hämäläinen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%